Morfofisiologia do capim-aruana pastejado por ovinos morada nova submetidos a quatro níveis de suplementação concentrada - Vasconcelos, Elayne Cristina Gadelha (2014)
This study evaluated the gas exchange, the biomass flow and the structural characteristics of Panicum maximum cv. Aruana grazed by Morada Nova sheep under rotational stocking and supplied with four concentrate supplementation levels (0.0; 0.6; 1.2 and 1.8% body weight), using four day-grazing periods and rest when the interception of 90% of the photosynthetic active radiation (PAR). The experiment was a completely randomized split-plot design with supplementation levels as plots and grazing cycles as subplots. The post-grazing condition consisted of a leaf area index of 1.0. We observed an increasing linear effect for stem elongation rate and leaf appearance rate according to the supplementation levels. The production and accumulation rates of forage also increased according to the supplementation levels. The different grazing cycles affected the variables of gas exchange of the recently expanded leaves, namely transpiration, stomatal conductance, leaf photosynthesis rate. In turn, no significant effect was detected for the gas exchange variables of emergent leaves. Biomass components during the post-grazing period showed a significant effect of the interaction between supplementation levels and grazing cycles for residual green forage biomass (BFVr), residual green leaf biomass (BLVr), residual green stem biomass (BCVr) and residual leaf:stem ratio (F_Cr). All these variables, with the exception of F_Cr, presented a quadratic effect in the cycles two and three, confirming the substitutive effect from the supplementation level of 0.86%, with the minimum estimated at 257.53 Kg•ha-¹•year-1, for BLVr. The ratio between living and senescent material showed an increasing linear response as a function of the supplementation levels. The pasture height and the residual tiller population density were affected only by grazing cycles. Green forage biomass (BFV) and green leaf biomass (BLV) presented a quadratic effect of the supplementation levels and grazing cycles. BLV showed a quadratic effect for the cycles two and three, where the higher values were 1489.47, at the level of 0.62, in the second cycle, and 1554.95 Kg•ha-¹•year-1 in the third cycle with a supplementation level of 0.14%. Gas exchange was not influenced by the supplementation levels. Morphogenetic traits of the aruana grass pasture are linearly affected by increasing levels of supplementation. The structural components of the aruana grass pasture are influenced by the increasing levels of concentrate supplementation, with a substitutive effect of the supplement.